2016
DOI: 10.1270/jsbbs.16025
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the SSIIa <i>null</i> mutations on grain traits and composition in durum wheat

Abstract: Starch represents a major nutrient in the human diet providing essentially a source of energy. More recently the modification of its composition has been associated with new functionalities both at the nutritional and technological level. Targeting the major starch biosynthetic enzymes has been shown to be a valuable strategy to manipulate the amylose-amylopectin ratio in reserve starch. In the present work a breeding strategy aiming to produce a set of SSIIa (starch synthases IIa) null durum wheat is describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 37 publications
6
46
0
Order By: Relevance
“…Yield reductions in ssIIa triple mutant lines are most easily explained by the significant reduction in starch and kernel weight for all mutant haplotypes across both years (Table III). A decrease in kernel weight has been reported in ssIIa null lines in barley, bread, and durum wheat (Morell et al 2003; Clarke et al 2008; Konik‐Rose et al 2007; Hogg et al 2015; Rakszegi et al 2015; Botticella et al 2016). Decreases in kernel weight in the high‐amylose lines are attributable to the decrease in starch content evident in the positive correlation between kernel weight and starch content ( r = 0.70) (Tables III and IV).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Yield reductions in ssIIa triple mutant lines are most easily explained by the significant reduction in starch and kernel weight for all mutant haplotypes across both years (Table III). A decrease in kernel weight has been reported in ssIIa null lines in barley, bread, and durum wheat (Morell et al 2003; Clarke et al 2008; Konik‐Rose et al 2007; Hogg et al 2015; Rakszegi et al 2015; Botticella et al 2016). Decreases in kernel weight in the high‐amylose lines are attributable to the decrease in starch content evident in the positive correlation between kernel weight and starch content ( r = 0.70) (Tables III and IV).…”
Section: Discussionmentioning
confidence: 91%
“…The effect of increased amylose upon wheat kernel hardness is not well described. In durum wheat, which lacks the Ha locus and is the hardest class of wheat, Hogg et al (2015) found a ssIIa null line with increased amylose remained very hard but was significantly softer in kernel texture compared with its wild‐type sister line, whereas Botticella et al (2016) found no correlation between amylose content and grain hardness. In “waxy” durum wheats, which lack amylose owing to wx‐1 null mutations, results are also mixed, with Vignaux et al (2004) finding no relationship between amylose and grain hardness, whereas Grant et al (2004) found the wx‐1 null lines were softer compared with control cv.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in sucrose SRCs for ssIIa mutants indicates elevated levels of non‐starch polysaccharides in the flour (Kweon et al, ). The increase in non‐starch polysaccharides can partially be attributed to the increased bran in the flour but elevated levels of other polysaccharides such as fructan, arabinoxylan, and beta‐glucan have been reported in SSIIa nulls in hexaploid wheat, durum wheat, and barley (Clarke et al, , Shimbata et al, , Botticella et al, ; Li et al, ; Botticella et al, ). Lactic acid SRCs showed there was an increase in absorption in ssIIa mutant combinations 1 and 2 compared to controls but similar values between mutant and wild type for combinations 3 and 4, which would indicate the functionality of gluten in ssIIa mutants and wild types, are comparable when analyzed independently (Kweon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been observed in durum wheat ( Triticum turgidum sp . durum ) (Botticella et al, ; Hogg et al, ; Hogg, Martin, Manthey, & Giroux, ) and barley ( Hordeum vulgare ) (Morell et al, , Clarke et al, , Regina et al, , Sparla et al, ).…”
Section: Introductionmentioning
confidence: 99%